Investing in your 20s & 30s for dummies - Tyson, Eric (Eric Kevin). (Hoboken, N.J. : John Wiley & Sons, 2013)
Covering everything from evaluating assets and managing risk to demystifying your portfolio, this guide offers expert invest advice that you shouldn't be without.
Introduction -- Understanding investing terms and concepts -- Preparing your investing foundation -- Beginning investments -- Advanced investments -- The part of tens.
Includes index.
Keywords: Investments; Finance, Personal; Young adults -- Finance, Personal